Business Sustainability, Reporting and Economic Consequences : The Case of a Developing Country – Malaysia - Lee, Ling Kim (2016)
The Government of Malaysia has been actively propagating Business Sustainability Initiative (BSI) to Malaysian organisations vide its representative agencies. Nonetheless, research results found that the BSI practices among Malaysian organisations remained nascent (PwC, 2013; Lu and Castka, 2009). Hence, the main objective of this study is to identify the determinants which may influence whether an organisation is an active participant of BSI or otherwise. The next study area looks at whether organisations will engage their stakeholders consistently if they are aware of the associated benefits. A final study area covers whether organisational stakeholders in Malaysia will consider BSI factors when they make business or investment decisions. Data for the abovementioned study areas are collected via an online questionnaire with 104 respondents of various different backgrounds. Overall, depending on the type of BSI, the results have indicated that the participation of Malaysian organisations in BSI is influenced by several factors, including organisational-specific characteristics, institutional and environmental characteristics, pressures from stakeholders as well as the potential benefits and challenges associated. In addition, organisations are likely to engage their stakeholders constantly if benefits are promised. It is also found that sustainability reports remained the main information platform for stakeholders to obtain BSI information when they make decisions.